Redistributive Impact of GST Tax Reform: Pakistan, 1990-2001 (The Pakistan Development Review, 2005)
Pakistan has undergone a significant change in tax structure over the last fifteen years. However, this change is not apparent on the surface, as there has not been much change in the tax to GDP ratio over the last fifteen years. But if we look beyond the surface we can see changes, for example in (1990-91), indirect taxes contributed 82 percent of total tax revenue with Customs, Excise and Sales tax each contributing around 55, 28 and 18 percent respectively, while in (2001-02), indirect tax share within the total tax revenue fell slightly to 68 percent with Customs, Excises and Sales tax each now contributing around 18, 18 and 64 percent respectively. Thus, it may not be wrong to say that there has been a significant change in the tax mix in the span of less than ten years and this development is important from the perspective of efficiency, effectiveness and equity with which revenues have and will be raised. Although, Value Added Tax (VAT) is likely to be more efficient in raising revenue than both the ordinary Sales Tax and Trade Taxes that it has replaced see e.g. [Nellor (1987); Liam Ebrill (2001)], the same cannot be said as far as the fairness issue is concerned. This in no way implies that the trade taxes replaced by VAT were more fair. However in most developing countries they operate with strict import licensing schemes, binding quotas and foreign exchange restrictions that make them more a kin to lump sum tax. Therefore in most cases they have no flow through effect to the consumers [for example see Clarete (1986); Shah (1991)]. But in contrast to this VAT being a consumption tax has the capacity to directly affect each and every household. Thus equity becomes much more of a real concern and this concern is heightened given that governments of most of the developing countries lack the capacity to carry out significant redistribution.